Kondisi Fisik Rumah Pendertia Tuberkulosis Paru di wilayah Pedesaan Kabupaten Sampang - Ahmadi, Ahmadi; Elok Alfiah Mawardi; Mei Lestari Ika Widyyati; Rizki Hidayati (Indonesian Health Science Journal, 2025)
Introduction: Tuberculosis (TB) is still a global health problem, especially in developing countries such as Indonesia. Home environmental factors play an important role in the spread of this disease. Poor ventilation, lack of lighting, and high occupancy density can increase the risk of infection. Research objectives: This study aims to evaluate the conditions of the home environment related to the risk of TB spread. Methods: This study uses a descriptive design with a quantitative approach. Measurements were made on 85 homes using roll meters, lux meters, and thermohygrometers to assess ventilation area, lighting, floor type, humidity, occupancy density, and room temperature. The analysis was carried out descriptively to determine the percentage of houses that met or did not meet environmental health standards. Results: The results of the study showed that most homes did not meet environmental health standards. As many as 81.2% of houses have inadequate ventilation, 71.1% have less than standard lighting, and 77.6% have high residential density. In addition, 84.7% of homes had humidity outside the ideal range, 82.4% had inappropriate room temperatures, and 60% of homes had floors that were not waterproof. Conclusion: Poor home environmental conditions contribute to the risk of TB spread. Interventions are needed in the form of community education, improvement of ventilation and lighting, and reduction of residential density to create a healthier environment.